Indonesian National Policy of Criminal Law in Enforcing Law Against Illegal Logging of Conservation Forest Timber - Nurmala, Leni Dwi (Jurnal Dinamika Hukum, 2024)
Abstract Crime in the forestry sector in the form of illegal felling of trees creates problems that are quite complicated to overcome. Tree felling in Indonesia is one of the cases most frequently handled by the Environmental and Forestry Law Enforcement Service. Illegal logging leads to deforestation and a decrease in the size of state forests. This article aims to discuss law enforcement against illegal logging crimes and how national laws can reduce the occurrence of these crimes. This research uses a normative juridical approach, namely a study of statutory regulations as primary data supported by secondary data using a literature review. The findings of this research are that in law enforcement efforts to respond to these crimes, the Indonesian Government has implemented regulatory provisions that have been stated firmly in the Prevention and Combating of Forest Destruction Law (2013), which have comprehensively provided opportunities for regional governments through the distribution of central government authority, as well as the involvement of the community and legal agencies or corporation that has a permit to manage forest products in an effort to prevent and eradicate illegal logging crimes, imposing consequences on wrongdoers through incarceration, criminal fines, and administrative penalties. However, the legal policies in this law have not effectively reduced the occurrence of crime because other regulations still contain policies that open up opportunities for illegal logging. Therefore, synchronization between regulations and laws related to forestry issues is required. Keywords: criminal sanctions; Illegal logging; law enforcement.